2017
DOI: 10.1007/s10750-017-3201-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of mangrove forest in reducing coastal inundation during major hurricanes

Abstract: A vegetation-resolving CH3D-SWAN surge-wave modeling system is used to examine the role of mangroves and salt marshes along the shore of Biscayne Bay in buffering surge, wave, and inundation in Southeast Florida during Hurricane Andrew (1992). First, the 3D vegetation-resolving model is validated by comparing the simulated and measured high water marks from post-hurricane field survey, debris lines, and time series of water level at the Haulover Pier. The simulated water levels and magnitude and extent of maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Recent expansion of mangroves into saltmarshes is likely to have large impacts on the structure, function and service provisioning of coastal wetlands (Kelleway et al, 2017). Although mangrove encroachment may increase nutrient storage and improve storm protection (Sheng & Zou, 2017), Kelleway et al (2017) hypothesized that declines will occur in habitat availability for fauna requiring open vegetation structure, as well as in the recreational and cultural activities associated with this fauna. They further project that the impact on provisional services such as fisheries productivity and cultural services will be site-specific and dependent on the species involved (Kelleway et al, 2017).…”
Section: Potential Mangrove Gains Due To Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Recent expansion of mangroves into saltmarshes is likely to have large impacts on the structure, function and service provisioning of coastal wetlands (Kelleway et al, 2017). Although mangrove encroachment may increase nutrient storage and improve storm protection (Sheng & Zou, 2017), Kelleway et al (2017) hypothesized that declines will occur in habitat availability for fauna requiring open vegetation structure, as well as in the recreational and cultural activities associated with this fauna. They further project that the impact on provisional services such as fisheries productivity and cultural services will be site-specific and dependent on the species involved (Kelleway et al, 2017).…”
Section: Potential Mangrove Gains Due To Climate Changementioning
confidence: 99%
“…While these potential gains do not nearly balance out continued anthropogenic losses, they tell us that the true state of the world's mangroves is more nuanced than scientists, managers, and policy makers sometimes communicate. Continued research on the basic biology and hydrology of mangroves is critical (Contreras et al, 2017;Lovelock et al, 2017b;Pérez et al, 2017), as well as the provisioning (Benzeev et al, 2017;Palacios & Cantera, 2017) and regulating ecosystem services Kamal et al, 2017;Sheng & Zou, 2017) they provide, because the interplay between mangrove expansion and biological requirements can manifest at very small spatial scales. There is a particularly active research community focusing on the role of mangrove invertebrates and their biology (Bakkar et al, 2017;Castellanos-Galindo et al, 2017;Fusi et al, 2017;Hendy & Cragg, 2017;Pestana et al, 2017;Raw et al, 2017;Saintilan & Mazumder, 2017).…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data show that from 1995 to 2006 the coastline in the study area retreated to 293 m and there had been loss of some land (Nugraha 2015;Tamba 2016). Damage to natural barriers in the form of mangrove forests (Akbar et al 2017;Sheng & Zou 2017;Syahputra, et al 2018;Soeprobowati et al 2020) also affects the rate of flood inundation in Semarang City (Ikhsyan 2017). While the level of mangrove vegetation density has not yet recovered and there is not enough budget allocation for infrastructure development in the form of embankments, breakwater walls and puddle water disposal pumps make the threat of flooding continues to occur, resulting in an increasing number of losses suffered by the community.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Therefore, in this study, CH3D is dynamically coupled to SWAN (Booij et al 1999) to simulate surge, wave, and flooding in high-resolution coastal region, while ADCIRC and WaveWatch-III (Tolman 2009) are used to provide offshore open boundary conditions for CH3D and SWAN, respectively. This integrated storm surge modeling system, CH3D-SSMS (Sheng et al 2006), is capable of simulating flooding and drying and has been used extensively for simulating and forecasting numerous storm surges along the US Atlantic and Gulf coasts (e.g., Sheng et al 2010a, b;Davis et al 2010;Paramygin et al 2016;Sheng and Zou 2017). In a US Southeastern Regional Storm Surge Model Testbed (Sheng et al 2012a), it was found that CH3D-SSMS was the most efficient high fidelity surge model, following closely behind the low fidelity SLOSH model, while possessing similar accuracy as other high fidelity models.…”
Section: Modeling Systems and Study Domainsmentioning
confidence: 99%